ANXIETY ON LISTENING COURSE AMONG STUDENTS DURING THE PANDEMIC OF COVID -19 - Muhammad Rafli Pratama; Neni Nurkhamidah (JETAL: Journal of English Teaching & Applied Linguistic, 2023)
Students had to continue learning activities at home during the pandemic, including listening classes. Unfortunately, several factors interfered with student comprehension in online courses and caused students to experience anxiety. This study aimed to identify several factors contributing to students' listening anxiety and discover strategies to overcome their anxiety in listening classes. This study included 30 students from SMPN 245 in Jakarta. To collect data, the researcher applied a descriptive qualitative method. The researcher used an interview as the instrument of this research. The researcher found that 22 participants of the interview experienced anxiety due to high-speed rate, concentration difficulties, lack of confidence, and nervousness. Other factors impacting students' comprehension are internet connections problem, noisy environments, and unsupportive devices. In this research, the researcher also provided several strategies students may employ to overcome anxiety.